Influence of deflectors on indoor airflow velocity distribution under natural ventilation conditions - Wang, Chaojie; Jin, Meng; Cheng, Haifeng (Frontiers in Energy Research, 2024)
Deflectors offer a cost-effective solution for enhancing airflow distribution. The purpose of this paper is to investigate the effect of the deflector on the indoor airflow velocity distribution under natural ventilation conditions. The results obtained from numerical simulations are validated through experimental measurements using a reduced-scale model. Subsequently, the validated reduced-scale numerical model was extended to full-size rooms. A full-size numerical simulation method is used to analyze the effect of no deflector, deflectors with different opening width-to-height ratios and deflectors with different opening shapes on the percentage of indoor velocity partitions under natural ventilation conditions. The findings reveal that the judicious installation of deflectors can enhance indoor airflow velocity distribution and increase the percentage of the indoor comfort zone. Deflectors with different opening width-to-height ratios exert distinct influences on indoor airflow velocity distribution. When the deflector opening width-to-height ratio is set at 7/6, the indoor comfort zone percentage reaches its maximum at 75.98%. Furthermore, the shape of the deflector's opening significantly affects indoor airflow velocity distribution, and when the opening shape is a rhombus shape of 4.00 cm × 9.00 cm, the proportion of indoor velocity comfort zone is the largest, which is 75.56%. This study provides a reference for the design and practice of natural ventilation in buildings.